HLA-B27 and B27-Subtypes in the Pathogenesis of Ankylosing Spondylitis - Feltkamp, T. E.W. (Current Rheumatology Reviews, 2005)
Ankylosing spondylitis (AS) is so strongly associated with the genetical marker HLA-B27 that the molecule is supposed to play a central role in the pathogenesis of the disease. If this is true, it has to be explained why there is such a difference in pathogenic consequences between certain subtypes of HLA-B27. The subtypes B*2706 and B*2709 play probably no pathogenic role, this in contrast to other subtypes like B*2704 and B*2705 for which such a role is evident. The difference between pathogenic and non-pathogenic subtypes is small and limited to the amino acid residues 114 and 116 on the antigen presenting groove of the molecule. The non-pathogenic molecule HLA-B*2706 has, in contrast to all HLA-B27 molecules associated with the disease, aspartic acid on position 114. This amino acid residue is situated on the rim between the D and the F pocket. The molecule B*2709 has histidine on position 116 on the bottom of the F pocket, which is unique. These small but significant differences were the subject of studies by Ringrose and Lopez de Castro. Ringrose studied the bacterial antigen presenting capacity of HLA-B*2704, but was not already able to compare it with that of B*2706 [1]. Lopez de Castro and his co-workers compared B*2704 and B*2706. They showed that arginine at position 3 of peptides is better presented by B*2706 than by B*2704, whereas alanine and tyrosine at this position show the opposite [2]. These studies have to proceed and will help to reveal how these small differences can be responsible for the difference between health and disease.
Keywords: indonesia